1995
DOI: 10.1254/jjp.68.323
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Action of the β-Adrenoceptor Antagonist Bopindolol and Its Metabolite 18-502

Abstract: ABSTRACT-Theantioxidative effects of (3-adrenoceptor antagonists and related compounds were investigated. Among the (3-adrenoceptor antagonists, the agents with a potent membrane-stabilizing activity such as bopindolol and propranolol strongly inhibited the hydrogen peroxide (H202)-induced lipid peroxidation of liver microsomes. Fifty percent inhibition concentration values for the lipid peroxidation of bopindolol, 18-502 (metabolite of bopindolol) and propranolol were calculated to be 1.8 1M, 10 pM and 2.3 pM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…These results mean that landiol is able to enhance lipid peroxidation. This is supported by results from previous studies: acebutolol 23 and pindolol 24 enhanced the H 2 O 2 -induced lipid peroxidation in liver microsomes. Thus, it was speculated that landiolol itself may be able to increase ROS production directly.…”
Section: Discussionsupporting
confidence: 89%
“…These results mean that landiol is able to enhance lipid peroxidation. This is supported by results from previous studies: acebutolol 23 and pindolol 24 enhanced the H 2 O 2 -induced lipid peroxidation in liver microsomes. Thus, it was speculated that landiolol itself may be able to increase ROS production directly.…”
Section: Discussionsupporting
confidence: 89%
“…Bopindolol was found to have free radical scavenging activity; in this respect, it was more potent than propranolol (4). Aniya et al (4) suggested that this potent antioxidant activity of bopindolol may be useful in the treatment of various diseases caused by oxidative stress.…”
Section: Effects Of Bopindolol On Myocardial Ischemiamentioning
confidence: 99%